2018
DOI: 10.1016/j.wjorl.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

P‐glycoprotein and chronic rhinosinusitis

Abstract: Chronic rhinosinusitis (CRS) is a heterogeneous definition that includes different disease states that usually are associated with abnormal inflammatory responses. Besides being prevalent, the mechanisms involved in its pathogenesis are not clear and there are few therapeutic options with tolerable side effects. P-glycoprotein (P-gp) is an efflux pump responsible of extruding xenobiotics and cellular metabolites from multiple cell types. It has been widely studied in the cancer field, due to its ability to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Nocera et al proved that the median concentration of exosomal permeability-glycoprotein (P-gp), a transmembrane glycoprotein, was significantly enriched among CRSwNP patients relative to the HS group, but earlier, it was also determined that the mucus concentration of P-gp is significantly higher in CRS, particularly in CRSwNP [ 28 ]; therefore, both methods could be used noninvasively to determine the level of this biomarker. P-gp is an epithelial driver of type 2 inflammation [ 116 , 117 ], and its expression in SM increases after CST-1 exposure [ 20 ]. Furthermore, Nocera’s study was the first to present an epithelial transfer of autologous exosomes and their protein cargo, P-gp, within primary human samples [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nocera et al proved that the median concentration of exosomal permeability-glycoprotein (P-gp), a transmembrane glycoprotein, was significantly enriched among CRSwNP patients relative to the HS group, but earlier, it was also determined that the mucus concentration of P-gp is significantly higher in CRS, particularly in CRSwNP [ 28 ]; therefore, both methods could be used noninvasively to determine the level of this biomarker. P-gp is an epithelial driver of type 2 inflammation [ 116 , 117 ], and its expression in SM increases after CST-1 exposure [ 20 ]. Furthermore, Nocera’s study was the first to present an epithelial transfer of autologous exosomes and their protein cargo, P-gp, within primary human samples [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…P-glycoprotein (P-gp), an adenosine triphosphate (ATP)-dependent efflux pump expressed on different cell types, is known to be highly expressed in eosinophilic CRS and CRSwNP and is associated with multidrug resistance [ 105 , 106 ]. Gunel et al reported that a higher expression level of P-gp was found in CRS patients with osteitis than in those without osteitis [ 107 ].…”
Section: Tissue Remodelingmentioning
confidence: 99%
“…P-gp, also referred to as multidrug resistance protein, functions as an adenosine triphosphate-dependent efflux pump and is expressed in a variety of cell types, including both immune cells and epithelial cells. Patients with CRSwNP and eosinophilic CRSsNP had higher expression levels of P-gp in nasal mucosa than healthy controls [33][34][35]. It was demonstrated that P-gp exhibited immunomodulatory activity and affected the secretion of inflammatory cytokines and chemokines [36].…”
Section: Eosinophilic Remodelingmentioning
confidence: 99%